A Syntactic Analysis on Sentences Found in the English Textbook for the Tenth Grade Students Entitled “Bahasa Inggris Kelas X” (2017 revised edition) Published by Ministry of Education and Culture Republic of Indonesia - Liana Mumrikoh; Eka Agustina; Hastuti Retno Kuspiyah (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2019)
This study is an analysis of sentence structure by using a syntactic approach that portrayed in the tree diagram. This study focused only on the discussion covering the identification of types of sentence and sentence structure. It was found that there are 191 sentences from the six selected text in the textbook consisting of the simple sentence which has 53 sentences (27,75%), the compound sentence has 79 sentences (41,36%), the complex sentence has 33 sentences (17,27% ) and the compound-complex sentence has 26 sentences (13,61%) from the total number of the data. The finding of the analysis shows that the English textbook has all types of sentences, based on both several clauses and their syntactic properties. A drawing tree diagram is a fundamental skill in the study of syntactic structure; it is a common practice to provide a visual representation of the internal structure of phrase and clause. Tree diagrams are a clear way of representing syntactic structure graphically.